Compliments and Compliment Responses Used by English Teacher Association of Senior High School in Pacitan - Andi Pujian purnomo; hasan khalawi (LPPM Press, 2019)
This paper deals with pragmatics, the study of pragmatics on giving and responding to the compliments. The research was conducted to find the way respondents employ compliment and its response strategies for topics of appearance, possession, and skill or ability in difference status (equal, higher and lower). The focus here is the analysis of strategies uttered by English Teacher Association of Senior High School in Pacitan, consisting of 16 male respondents and 9 female respondents by means of DCT (Discourse Completion Task). The corpus used in this analysis is 450, consists of 225 compliments and 225 responses. The study highlights on the use of head acts and supportive moves based on Trosborg’s theory and Herbert’s taxonomy of compliment responses. The respondents participating in this research, females used more variation in giving compliment strategies than males. Both males and females mostly apply appreciation token for their compliment response strategies. The findings presented here should not be generalized and comparisons with results based on different types of data, situation, and respondents will lead to a better understanding.